ANALISIS STRUKTUR, PERILAKU, PENAMPILAN PASAR DAN EFISIENSI PEMASARAN KEDELAI DI KABUPATEN WONOGIRI - Eko Murniyanto; G Santoso; Suroto Suroto (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2008)
Expecial problems in agrobusiness is marketing system. Understanding of existing marketing system guarantee succecting agrobusiness pass marketing strategy. In this research analysis area ratio concentration (Kr), marketing channel, marketing margin (MP), producer share level (SPl) and other marketing channel (SPn) and also efficiency marketing of soy in Wonogiri regency